A Game Theoretic Model of Struggle with Corruption in Auctions: Computer Simulation - Kirill Kozlov; Guennady Ougolnitsky (Mathematics, 2022)
There is a great deal of literature devoted to mathematical models of corruption, including corruption in auctions. However, the relationship between the seller and the auctioneer is not studied sufficiently. The research aim is to analyze such relations in a game theoretic setup. We built a difference game theoretic model in normal form that describes possible collusion between an auctioneer and participants of an auction. The auctioneer acts on behalf of a seller. The seller can control possible collusions by administrative and economic mechanisms. The probability of detection depends on audit cost. We consider four cases of absence/presence of the collusion and those of the audit. The model is investigated numerically by simulation modeling using an original method of qualitatively representative scenarios. Several conclusions are made: factors of corruption are low probability of detection, small penalty, and big corruption gain of the auctioneer.